Barriers to kidney transplantation among patients on maintenance haemodialysis at the Jos university teaching hospital, Nigeria - V E Onowa; S I Shuaibu; C G Ofoha; A C Agbo; D G Uchendu; Z Gimba; E I Agaba; V M Ramyil (Nigerian Journal of Medicine, 2017)
INTRODUCTION: Chronic kidney disease (CKD) is a major public health problem. End-stage renal disease (ESRD), represents the final stage of CKD and is best treated by Kidney Transplantation. However Kidney Transplantation in Sub-Saharan Africa is beset by a myriad of problems. OBJECTIVE(S): To identify the limitations to kidney transplantation as the preferred option for treatment of ESRD among patients on maintenance haemodialysis at a tertiary-care hospital in Nigeria. MATERIALS AND METHODS: This was a questionnaire based descriptive, cross-sectional hospital-based study carried out in the dialysis unit of the Jos University Teaching Hospital, Jos, Nigeria over a 6 months period, from June to December,2015 RESULTS: A total of 39 patients were enrolled for the study. The mean age of the patients was 45.7 ± 14.6 years. There were 25(64.1%) male and 14(35.9%) female. Financial constraint was the main reason limiting kidney transplantation in 66.7% majority of the patients. Five patients (12.8%) were medically unfit either due to advanced age or presence of comorbidities while 3 (7.7%) patients could not find a compatible donor. Other reasons given for not having had kidney transplant include religious belief,and a previously failed kidney transplant. CONCLUSION: Whereas awareness of kidney transplantation is high among patients with ESRD on maintenance haemodialysis, financial constraint remains the main hindrance to kidney transplantation among patients with End Stage Renal Disease in our setting.